2014
DOI: 10.2106/jbjs.n.00460
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Revision Following Total Hip Arthroplasty: Metal-on-Conventional Polyethylene Compared with Metal-on-Highly Cross-Linked Polyethylene Bearing Surfaces

Abstract: Abstract:The results of randomized controlled trials and systematic reviews have suggested reduced radiographic wear in highly cross-linked polyethylene compared with conventional polyethylene in primary total hip arthroplasty. However, longer-term clinical results have not been thoroughly examined, to our knowledge. The purpose of this study was to compare the risk of revision for metal-on-conventional and metal-on-highly cross-linked total hip arthroplasty bearing surfaces with use of a distributed data netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…Our finding may result from a lack of data in our network meta-analysis to compare outcomes, but is in line with published evidence from six national and regional registries. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Our finding may result from a lack of data in our network meta-analysis to compare outcomes, but is in line with published evidence from six national and regional registries. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Paxton and colleagues compared metal-on-HXLPE with metal-on-conventional (non-cross-linked) polyethylene bearing surfaces and found that non-cross-linked polyethylene was not associated with significantly worse outcomes compared with metal on HXLPE (http://dx.doi.org/10.2106/JBJS.N.00460) 13 . While the estimate of the effect trended in the direction of higher revision occurrence with metal on non-cross-linked polyethylene, the difference was not significant (hazard ratio [HR], 1.20; 95% confidence interval [CI], 0.80 to 1.79).…”
Section: Multinational Investigations Of Hip Bearings and Fixationmentioning
confidence: 99%
“…Various of highly cross-linked polyethylene(HCLPE) liners (such as Marathon, Depuy; X3, Stryker; Longevity, Zimmer; XLPE, Smith and Nephew; and Acrom XL, Biomet) have been used extensively to decrease wear, osteolysis and related implant failures in THA. Studies[35] have also shown that HCLPE has much less wear and osteolysis than does CUHMWPE. But long-term result of HCLPE in revision THA is unknown.…”
Section: Introductionmentioning
confidence: 99%